2020
DOI: 10.1002/mc.23260
|View full text |Cite
|
Sign up to set email alerts
|

Cancer biology functional genomics: From small RNAs to big dreams

Abstract: The year 2021 marks the 20th anniversary of the first publications reporting the discovery of the gene silencing mechanism, RNA interference (RNAi) in mammalian cells. Along with the many studies that delineated the proteins and substrates that form the RNAi pathway, this finding changed our understanding of the posttranscriptional regulation of mammalian gene expression. Furthermore, the development of methods that exploited the RNAi pathway began the technological revolution that eventually enabled the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 239 publications
(394 reference statements)
0
7
0
Order By: Relevance
“…Regarding RNAi, hereditary transthyretin amyloidosis and acute hepatic porphyria can already benefit from treatment options ( 137 ). Nevertheless, for the treatment of cancer, RNAi and ncRNA formulations have not yet been approved.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding RNAi, hereditary transthyretin amyloidosis and acute hepatic porphyria can already benefit from treatment options ( 137 ). Nevertheless, for the treatment of cancer, RNAi and ncRNA formulations have not yet been approved.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we performed an RNAi-based genetic screen targeting the entire degradome in two murine breast cancer cell lines for an unbiased identification of proteases important for breast cancer cell proliferation and/or survival. Genetic screens are a widely used tool to efficiently discover cancer drivers, novel cancer-linked genes, and putative therapeutic targets ( 1 , 2 , 31 ), but genome-wide ( 4 6 ) or kinase-focused screens ( 7 9 ) missed out on proteases so far.…”
Section: Discussionmentioning
confidence: 99%
“…Short hairpin RNA (shRNA) library-based RNA interference (RNAi) is a widely used method for large-scale genetic loss of function screens, allowing for the unbiased discovery of cancer drivers, putative therapeutic targets, and genes with no previous links to cancer (1)(2)(3). shRNA libraries contain a heterogeneous mixture of different shRNA constructs targeting the whole genome (genome-wide screening) or a subset, i.e., all kinases, in so-called focused libraries.…”
Section: Introductionmentioning
confidence: 99%
“…Many successful strategies have been developed by rational design using high throughput screenings, especially based on -omics data-integration approaches and genome-wide siRNA screening [ 51 , 52 ]. Furthermore, it is important to highlight that siRNA-based methods are helpful in the context of understanding the complex basis of a number of diseases such as cancer, infection, HIV [ 53 ], neurodegenerative and respiratory diseases. Since 2001, thousands of cancer-based studies have reported the employment of siRNA-based methods to study mammalian gene function, leading to the discovery of many genes with no previous links to cancer biology, for example, and enhanced understanding of the functions of established oncogene and tumor suppressors [ 54 ].…”
Section: Pros and Cons For The Broader Use Of Sirnas Into Clinicsmentioning
confidence: 99%